Is There a Link Between Green Human Resource Management and Consumer Buying Behavior? The Moderating Role of Employee Diffidence - Xiao, Yunxia; Younus, Rabia; Saeed, Wizra; Ul Haq, Junaid; Li, Xiuwen (Frontiers in Psychology, 2022)
Green HRM supports promoting and incorporating sustainable development of their resources. Managers and customers actively utilize the limited resources efficiently and effectively to accomplish environment-friendly goals and objectives. The study focuses on investigating the moderating role of diffidence between Green HRM, eco-friendly behavior and Employee Performance of frontline employees of the hospitality sector. Two hundred ten individuals participated in the research to observe green HRM policies of employees and their influence on consumer behavior. Besides, consumers gave their opinion on consumer buying behavior. The study's findings revealed that Green human resource management, aka Green HRM, directly impacts consumer behavior. In addition, diffidence moderates the relationship between Green HRM and employee performance and employee eco-friendly behavior.